Avtonomizem in egalitarizem po slovensko - Toplak, Cirila (Teorija in praksa, 2019)
This article is based on the premise that co-management and self-organising principles are "autochthonous" political traditions, i.e. typical historical forms of social organisation in Slovenian-speaking lands. Subsequently, autonomism and egalitarianism may be regarded as typical ideological backgrounds of Slovenian political culture. The author verifies this thesis by applying the micro-historical method as well as certain theories from the field of post-colonial studies, in particular to seek to identify the primordial form of Slovenian social organisation by a perspectivist translation of cultural differences, and to subsequently assess Slovenian society's capacity to conserve and reflect on its authentic political traditions. With this aim in mind, a case study of the local history of political organising in northwestern Slovenia is explained, where the retrospectively registered oral tradition is confronted with the "exterior" view by local written sources on the same topic. In response to the initial research questions, the author concludes that it is necessary to conceptually differentiate between traditional local autonomisms and the nationalist idea of autonomism produced by the modern imagined national community, and that the Slovenian concept of egalitarianism has always been restrained by patriarchy. Nevertheless, the era of Yugoslav socialist self-management is seen as being the greatest rapprochement between the primordial and state forms of social organisation and thereby the period of the greatest capacity of Slovenian society to think itself autonomously, as shown by the quality of social criticism produced by Yugoslav theoreticians at the time.
Keywords: Autonomy; Avtonomija; egalitarizem; politična zgodovina; posoško naravoverstvo; Samoupravljanje; Self-management by employees